PENGARUH PENGALAMAN PRAKTIK KERJA LAPANGAN (PKL) DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI TERHADAP KESIAPAN KERJA SISWA KELAS XII SMKN 1 LAMONGAN - Dian Aries Maulani; Novi Marlena (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This study aims to analyze the effect of Field Work Practice (PKL) experience on the work readiness of twelfth-grade students at SMKN 1 Lamongan with work motivation as a mediating variable. The research employed a quantitative approach with a causal associative design. The population consisted of 214 twelfth-grade students from the Business and Management program who had participated in PKL, with 139 respondents selected using proportionate random sampling. Data were collected through closed-ended questionnaires using a Likert scale. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results showed that PKL experience had a positive and significant effect on work readiness. PKL experience also had a significant effect on work motivation. In addition, work motivation significantly influenced work readiness. The indirect effect test indicated that work motivation significantly mediated the relationship between PKL experience and work readiness. These findings indicate that better PKL experience supported by high work motivation can improve students’ work readiness in facing the business and industrial world.